2018
DOI: 10.1101/490409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seeing emotions, reading emotions: behavioral and ERPs evidence of the effect of strategy and of regulation for pictures and words.

Abstract: ¶ These authors contributed equally to this work. AbstractBackground: Whilst there has been extensive study of the mechanisms underlying the effect of regulation for the emotions elicited by pictures, the ability and the mechanisms beyond the regulation of words remains to be clarified. Similarly, the effect of strategy when applying a regulatory process is still poorly explored. The present study seeks to elucidate these issues comparing the effect of regulation and of strategy to both neutral and emotional w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(115 reference statements)
2
0
0
Order By: Relevance
“…The subsequent broad centro-parietal positive deflection (i.e., P3) occurs between 300 and 600 ms after stimulus onset (Roche et al, 2004;Polich, 2007), and is thought to be generated by a more distributed network of cortical regions, relative to N2 (Polich, 2007;Foti and Hajcak, 2008;Hajcak, 2009, 2010). P3 amplitude is sensitive to motivationally salient stimuli, as it is modulated by both pleasant and unpleasant cues, regardless of whether the salience is defined in terms of the task demand or stimulus content (Olofsson et al, 2008;Hajcak et al, 2010;Weinberg and Hajcak, 2010); similar results have been reported for emotional words (Naumann et al, 1992) and faces (Allison et al, 1999;Grecucci et al, 2018;Sulpizio et al, 2019). Finally, the late positive potential (LPP) is a sustained positive deflection in the ERP waveform with centroparietal distribution, which emerges at approximately 300 ms following stimulus onset and persists for the duration of the stimulus (Schupp et al, 2000(Schupp et al, , 2004aFoti et al, 2009) and beyond (for as long as 1,000 ms) (Hajcak and Olvet, 2008;Hajcak et al, 2010).…”
Section: Introductionsupporting
confidence: 68%
“…The subsequent broad centro-parietal positive deflection (i.e., P3) occurs between 300 and 600 ms after stimulus onset (Roche et al, 2004;Polich, 2007), and is thought to be generated by a more distributed network of cortical regions, relative to N2 (Polich, 2007;Foti and Hajcak, 2008;Hajcak, 2009, 2010). P3 amplitude is sensitive to motivationally salient stimuli, as it is modulated by both pleasant and unpleasant cues, regardless of whether the salience is defined in terms of the task demand or stimulus content (Olofsson et al, 2008;Hajcak et al, 2010;Weinberg and Hajcak, 2010); similar results have been reported for emotional words (Naumann et al, 1992) and faces (Allison et al, 1999;Grecucci et al, 2018;Sulpizio et al, 2019). Finally, the late positive potential (LPP) is a sustained positive deflection in the ERP waveform with centroparietal distribution, which emerges at approximately 300 ms following stimulus onset and persists for the duration of the stimulus (Schupp et al, 2000(Schupp et al, , 2004aFoti et al, 2009) and beyond (for as long as 1,000 ms) (Hajcak and Olvet, 2008;Hajcak et al, 2010).…”
Section: Introductionsupporting
confidence: 68%
“…The subsequent broad centro-parietal positive deflection (i.e., P3) occurs between 300 and 600 ms after stimulus onset (Roche et al, 2004;Polich, 2007), and is thought to be generated by a more distributed network of cortical regions, relative to N2 (Polich, 2007;Foti and Hajcak, 2008;Hajcak, 2009, 2010). P3 amplitude is sensitive to motivationally salient stimuli, as it is modulated by both pleasant and unpleasant cues, regardless of whether the salience is defined in terms of the task demand or stimulus content (Olofsson et al, 2008;Hajcak et al, 2010;Weinberg and Hajcak, 2010); similar results have been reported for emotional words (Naumann et al, 1992) and faces (Allison et al, 1999;Grecucci et al, 2018;Sulpizio et al, 2019). Finally, the late positive potential (LPP) is a sustained positive deflection in the ERP waveform with centroparietal distribution, which emerges at approximately 300 ms following stimulus onset and persists for the duration of the stimulus (Schupp et al, 2000(Schupp et al, , 2004aFoti et al, 2009) and beyond (for as long as 1,000 ms) (Hajcak and Olvet, 2008;Hajcak et al, 2010).…”
Section: Introductionsupporting
confidence: 58%